Forty Years of Wildland Urban Interface Growth and Its Relation With Wildfires in Central-Western Chubut, Argentina - Godoy, Maria Marcela; Martinuzzi, Sebastián; Masera, Pablo; Defossé, Guillermo E. (Frontiers in Forests and Global Change, 2022)
Wildland Urban Interface (WUI) areas are rapidly expanding worldwide. In many regions of the world, this expansion could be explained by the increasing possibilities of telecommuting and developing home-office work, while at the same time living in, or surrounded by, wilderness areas of magnificent beauty. However, growth and development of these WUIs are still not well dimensioned and regulated, especially in fire prone ecosystems. Over the last two decades, an increasingly number of megafires occurred in these WUI areas in different regions of the world. Recently, big megafires occurred in WUIs located around towns in the western Andean-Patagonian region of Argentina. In this study, we analyzed the evolution of the WUI and its relationship with wildfires around cities and towns located in the northwestern part of Chubut province of Argentina. The studied region covers 325,273 ha and includes the cities of Esquel and Trevelin, and other small villages. Our objectives were to (i) map the current WUI, (ii) quantify changes occurred in the WUI in the last 40 years around the main cities of the region, and (iii) analyze the relationships among WUIs, vegetation types and wildfire occurrence. We mapped the distribution of WUI using spatially explicit information on housing density derived from censuses and high-resolution imagery from 1981/82 and 2021, and land cover data. The current WUI covered 8% of the study area, however it has 97% of the houses. Between 1981 and 2021, the WUI area increased by 80%, especially in the southern part of our study region. Finally, information on wildfires distribution revealed that 65% of the ignition points of the recent fires in the region occurred within the WUI. Most of the vegetation burned were herbs, sub-shrubs and woodlands. WUI expansion in our study area appears to be constrained by terrain features (slopes, accessibility), but not by vegetation characteristics. Our study suggests that continuing, unplanned housing expansion in wilderness areas without appropriate vegetation management will likely increases wildfire risk and human environmental conflicts further. Effective land use planning and wildfire management are crucial for sustainable housing expansion in western Patagonia.